GAMBARAN DISIPLIN DAN BUDAYA KERJA TERHADAP PERILAKU KEWARGAAN ORGANISASIONAL KARYAWAN PT. INTI (PERSERO) DI BANDUNG - Pratiwi, Ngindi Fadhilah; Senen, Syamsul Hadi; Sumiyati, Sumiyati (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this research is to know the decription of dicipline, work culture and organizational behavior citizenship.Design/methodology/approach - The Research design is cross sectional. This research is using descriptive approach with explanatory survey method. The analysis unit is 90 employees. Collecting the data is using questionnaire. Analysis technique used is descriptive technique with using frequency distribution.Finding - Based on the result of research, the results obtained that work dicipline in the category is appropriate with a score 65,5% , work culture is in the high category with a score 72,8%, and organizatonal citizenship behavior is in high category with a score 66,2%.Originality/value - This research giving a basic for understanding work dicipline, work culture and issues on organizatonal citizenship behavior. The difference of this research with the previous research are on the object, variable, theory and references